Impact of COVID-19 on the Life of Higher-Education Students in Istanbul: Relationship Between Social Support, Health-Risk Behaviors, and Mental/Academic Well-Being - YORGUNER, NEŞE; AKVARDAR, YILDIZ (AVES, 2021)
Objective:This study aimed to draw a general picture of the impact of the coronavirus disease 2019 (COVID-19) pandemic on the life of higher-education students in Istanbul, with specific emphasis on the relationship between students' social support systems, health-risk behaviors, and mental/academic well-being. Methods: A total of 2583 higher-education students from different fields of study participated in an online survey gathering information from several domains, including available social networks, support-seeking attitudes, substance use patterns, physical activity levels, academic stress, academic satisfaction, and psychological well-being during the pandemic. Results: Our findings pointed to major changes in students' life circumstances and daily routines during COVID-19, including a significant decrease in contact with friends, over-all substance use, and physical activity as well as high levels of depression, academic stress, and academic dissatisfaction. Depressive symptoms were significantly predicted by the loneliness score (OR= 2.08, 95% CI = 1.88-2.29), female gender (OR =1.65, 95% CI =1.21-2.24), frequency of binge drinking (OR =1.4, 95% CI = 1.06-1.86), and level of academic stress (OR =1.15, 95% CI =1.1-1.19), whereas the number of people to easily borrow money from was found to be a protective factor against depression (OR =0.95, 95% CI =0.92-0.99). Conclusion: Our results highlight the need for higher-education institutions to take the appropriate social and mental health interventions, tailored to fit the specific requirements of the COVID-19-related measures.
Keywords: COVID-19; health risk behaviors; social support; substance use; well-being; MENTAL-HEALTH; PHYSICAL-ACTIVITY; GENDER-DIFFERENCES; SUICIDAL IDEATION; SUBSTANCE USE; SELF-ESTEEM; ALCOHOL-USE; LONELINESS; DEPRESSION; UNIVERSITY